Shift-to-Shift Handoff Effects on Patient Safety and Outcomes: A Systematic Review. (January 2017) - Mardis, Matthew; Davis, Joshua; Benningfield, Branden; Elliott, Cater; Youngstrom, Mallory; Nelson, Brittany; Justice, Ellen M.; Riesenberg, Lee Ann
Multiple health care organizations have identified handoffs as a source of clinical errors; however, few studies have linked handoff interventions to improved patient outcomes. This systematic review of English-language research articles, published January 2008 to May 2015 and focusing on shift-to-shift handoff interventions and patient outcomes, yielded 10 774 unique articles. Twenty-one articles met inclusion criteria, measuring each of the following: patient falls (n = 7), reportable events (n = 6), length of stay (n = 4), mortality (n = 4), code calls (n = 4), medication errors (n = 4), medical errors (n = 3), procedural complications (n = 2), pressure ulcers (n = 2), weekend discharges (n = 2), and nosocomial infections (n = 2). One study each also measured time to first intervention, restraint use, overnight transfusions, and out-of-hours deteriorations. Studies that reported funding had higher quality scores. It is difficult to identify trends in the handoff research because of simultaneous implementation of multiple interventions and heterogeneity of the interventions, outcomes measured, and settings. The authors call for increased handoff research funding, especially for studies that include patient outcome measures.